Un décor exceptionnel du dernier tiers du XVIIe siècle découvert à Saint-Galmier dans la Loire : premiers jalons - Catherine Guillot (In Situ)
The Vernay fortified manor house at Saint-Galmier in the Loire department, to the north-east of Saint-Etienne, has a remarkable décor dating from the last third of the seventeenth century, situated in two ground-floor rooms of the building and in the passage joining the two rooms. The decor comprises painted models of virtues and landscapes, set in wooden panelling. The décor in the cabinet apparently takes its inspiration from the book published in 1642 by Georges and Madeleine de Scudéry Les Femmes illustres ou les Harangues héroïques, a homage paid to courageous women of Antiquity. The decors are painted in camaieu and seem to be the work of artists from northern Holland. The presence of some wallpaper also allows us to see something of the spread of designs produced in different French manufactories in about 1800